Antifungal Activity and Potential Mechanism of Panobinostat in Combination With Fluconazole Against Candida albicans - Su, Shan; Shi, Xiaohong; Xu, Wei; Li, Yiman; Chen, Xueqi; Jia, Shuang; Sun, Shujuan (Frontiers in Microbiology, 2020)
Invasive fungal infections are an emerging problem worldwide which bring huge health challenges. Candida albicans (C. albicans), the most common opportunistic fungal pathogen, can cause bloodstream infections with high mortality in susceptible hosts. At present, available antifungal agents used in clinical practice are limited, and most of them also have some serious adverse effects. The emergence of drug resistance because of the wide use of antifungal agents is a new limitation to successful patient therapy. Drug combination therapy is increasingly becoming a way to enhance antifungal efficacy, reduce drug resistance and potential toxicity. Panobinostat, as a pan-histone deacetylase (HDAC) inhibitor, has been approved by the US Food and Drug Administration (FDA) as novel antitumor agents. In this study, the antifungal effects and mechanisms of Panobinostat combined with fluconazole against C. albicans were explored for the first time. The results indicated that Panobinostat could work synergistically with fluconazole against resistant C. albicans, the minimal inhibitory concentrations (MIC) of Panobinostat could decrease from 128 to 0.5-2 μg/ml and the MIC of fluconazole (FLC) could decrease from >512 to 0.25-0.5 μg/ml, and the fractional inhibitory concentration index (FICI )value ranged from 0.0024-0.0166. It was not only synergized against planktonic cells, but also against C. albicans biofilms performed ≤8 h when Panobinostat combined with Fluconazole, the sMIC of Panobinostat could decrease from >128 to 0.5-8 μg/ml and the sMIC of FLC from >1,024 to 0.5-2 μg/ml, and the FICI value <0.5. The Galleria mellonella infection model was used to evaluate the in vivo effect of the drug combination, and the result showed that the survival rate could be improved obviously. Finally, we explored the synergistic mechanisms of the drug combination. The hyphal growth, which plays roles in drug resistance, was found to be inhibited, and metacaspase, which is related to cell apoptosis was activated (P < 0.01), while the synergistic effects were proven not to be related to the efflux pumps (P>0.05). These findings might provide novel insights into the antifungal drug discovery and the treatment of candidiasis caused by C. albicans.